STRATEGI PEMASARAN MELALUI LIVE INSTAGRAM TERHADAP PENJUALAN PADA TOKO AW STORE SITUBONDO - Maisaroh, Maisaroh; Rachman, Riza; Norchalicatin, Yuli; Anam, Muhammad Mishbahul; Indriani, Shafa Arina; Abaitunnisa, Fatima; Syaifurahman, Ahmad (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The AW store is a shop that operates in the thrift sector, where the shop sells various kinds of clothing such as shirts, trousers, and others. In marketing its products, the AW store carries out a marketing strategy, namely live Instagram. Live Instagram is a live broadcast activity on social media, especially Instagram. Where with live Instagram, sellers and buyers do not meet in person. Buyers can see what the AW store sells without having to come directly to the store.The research carried out was qualitative research, where data collection was obtained by means of interviews. The conclusion of this research is that the AW store carries out a marketing strategy for its store by means of live Instagram. This research shows that the live Instagram carried out by the AW store has had a big impact on increasing sales.